PENGARUH SIZE, LIKUIDITAS, RISIKO KREDIT DAN RENTABILITAS TERHADAP RASIO KECUKUPAN MODAL - Dewi, Ayusta Riana; Yadnya, I Putu (E-Jurnal Manajemen; Vol 7 No 7 (2018)DO - 10.24843/EJMUNUD.2018.v07.i07.p03, 2018)
BPR industry is needed in order to create financial system stability and fostering national economic growth.This study aims to determine the effect of bank size, Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) and Net Interest Margin (NIM) to Capital Adequacy Ratio (CAR). This research was conducted at BPR in Bali Province period 2015-2016. The sampling technique used census method amounting to 137 BPR with multiple linear regression analysis technique. Based on the results of the analysis shows that the Size / size of the bank has a significant negative effect on CAR. This shows that the higher total assets of a bank the higher the risk weight and capital adequacy will decrease. LDR and NIM have a significant positive effect on CAR. This indicates that the higher LDR and NIM then the capital adequacy will increase. NPL has a significant negative effect on CAR. This shows that the higher the NPL, the adequacy of bank capital will decrease Keywords : CAR, SIZE, LDR, NPL, NIM